Odpowiedzi

2009-11-23T21:10:53+01:00
A) (x+1)(x+2) = x2+2x+x+2=x2+3x+2
B) (3a+4)(a-5) = 3a2-15a+4a-20=3a2-11a-20
C) (2t+1)(1-3t)= 2t-6t2+1-3t=-6t2-3t+1
D) (3ab-7)(3-7ab) = 9ab-21a2b2-21+49ab=-21a2b2+58ab-21
2009-11-23T21:21:26+01:00
(x+1)(x+2)=x² +2x+x+2=x²+3x+2

(3a+4)(a-5)=3a²-15a+4a-20=3a²-11a-20

(2t+1)(1-3t)=2t-6t²+1-3t=-t-6t²+1

(3ab-7)(3-7ab)=9ab-21ab²-21+49ab=-21a²b²-21+58ab
2009-11-23T21:23:25+01:00
A) (x+1)(x+2)=x²+2x+x+2=x²+3x+2

B) (3a+4)(a-5)=3a²-15a+4a-20=3a²-11a-20

C) (2t+1)(1-3t)=2t-6t²+1-3t=-6t²-t+1

D) (3ab-7)(3-7ab)=9ab-21a²b²-21+49ab=-21a²b²+58ab-21